Self-care for the researcher: dark tourism in Varanasi, India - Sharma, Nitasha; Rickly, Jillian M. (Taylor & Francis, 2018)
Dark tourism is a popular niche of tourism that allows tourists to come into close proximity with death, atrocity, and the macabre, and therefore has the potential to be an emotional and even traumatic encounter for tourists. While this context has inspired tourism researchers to investigate dark tourists’ motivations, as well as the marketing and representation of dark tourism sites, we have yet to attend to its implications for the researcher. This paper analyzes the emotional experiences and aftermath of fieldwork at the cremation grounds of Varanasi, India, which involved working closely with tourists, Doms, and Aghoris by focusing on the relations of reflexivity, positionality, and emotionality. As a result, we suggest a number of reflexive and self-care practices to be put into place so as to attend to the researchers’ emotional well-being in the fieldwork process.